2011
DOI: 10.1161/circulationaha.111.042788
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Assessment of the Risk Profile of Evolving Individual Coronary Plaques

Abstract: T he natural history of coronary plaques within an individual patient with coronary disease is highly heterogeneous. Over time, each plaque may exhibit a different temporal pattern of progression, quiescence, or regression, as well as a variable rate of change. The trajectory of the natural history of a particular plaque depends on the level of systemic risk factors and patient-specific genetics, as well as local phenomena, such as the detailed local blood flow patterns, arterial wall characteristics, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…A large-scale natural history study (506 patients with 1-year follow-up), PREDICTION, evaluating the role of coronary WSS in patients with CAD has recently been completed. Preliminary results of the PREDICTION study are largely in keeping with our findings and show that low WSS is an independent predictor of worsening lumen narrowing, the need for percutaneous coronary intervention and is indicitaive of major adverse cardiac events at follow-up [15,16].…”
Section: "Translating the Mechanistic Link Between Wall Shear Stress supporting
confidence: 80%
“…A large-scale natural history study (506 patients with 1-year follow-up), PREDICTION, evaluating the role of coronary WSS in patients with CAD has recently been completed. Preliminary results of the PREDICTION study are largely in keeping with our findings and show that low WSS is an independent predictor of worsening lumen narrowing, the need for percutaneous coronary intervention and is indicitaive of major adverse cardiac events at follow-up [15,16].…”
Section: "Translating the Mechanistic Link Between Wall Shear Stress supporting
confidence: 80%
“…46 From a broader perspective, apart from controlling conventional atherosclerotic risks, in vivo studies of coronary artery disease have revealed the importance of other factors in plaque remodeling; patient-specific genetics, local hemodynamics and endothelial shear stress, arterial wall and remodeling characteristics, and plaque size and shape also played determining roles. 47,48 The diverging clinical and angiographic outcomes in our patients amid a relatively uniform risk factor control might reflect an intricate interplay of these factors. Although remodeling of intracranial plaques remains largely unknown, further studies of the natural history of ICAD are crucial for defining the indication and time window of any forthcoming treatment that aims to improve stenosis.…”
Section: Discussionmentioning
confidence: 86%
“…Thanks to rapid modeling, this methodology not only allows characterization of arterial plaque at a single point in time but, also allows prognostic insight into how plaques evolve over time 38 . If it were possible to recognize in vivo plaques that were expected to develop features of rupture prone lesions, specific interventions could be performed to avoid adverse cardiac event.…”
Section: Discussionmentioning
confidence: 99%